Effect of Al content on the thermal oxidation behaviour of AlHfMoNbTi high-entropy alloys analysed by in situ environmental TEM. (October 2021) - Yang, Xiaomeng; An, Zibing; Zhai, Yadi; Wang, Xin; Chen, Yanhui; Mao, Shengcheng; Han, Xiaodong
Graphical abstract: Highlights: The in situ oxidation behavior in an environmental TEM of Al contained HfMoNbTi high entropy alloys were studied and moderate Al addition was suggested for alloy design. Al in RHEA system can improves the oxidation resistance by reducing the thickness of the Mo-rich layer, and thus reduce the stress and spalling tendency in the oxide layer. Al contained RHEA forms mixed oxide layers rather than a specific Al2 O3 layer. It is recommended to use less Mo and other elements that produce volatile oxides to improve oxidation resistance. Abstract: The high-temperature oxidation behaviours of AlxHfMoNbTi-series refractory high-entropy alloys with an Al content ranging from 0 to 20 at.% (x=0-1) were tested at 700–1000 °C. An in situ oxidation experiment was performed at 25–900 °C using environmental transmission electron microscopy (ETEM) to reveal the oxidation mechanism. The addition of Al to the HfMoNbTi alloy effectively increased the alloy strength and hardness. The improvement in oxidation resistance by Al addition is attributed to the formation of mixed oxide structures instead of layered oxides. Mo-rich precipitates are preferentially oxidized, and their volatilization at the metal/oxide interface accelerates alloy oxidation.